A brief history of Christian worship - White, James F. (James Floyd), 1932- (Nashville, TN : Abingdon Press, 1993)
A history of Christian liturgy written from the perspectives of the 1990s in North America, covering a period that ranges from the New Testament era through modern times, with a look at the future of worship.
Worship in the churches of the New Testament era -- Worship in the churches of the early Christian centuries -- Worship in the churches of the middle ages -- Worship in the churches of the reformation period -- Worship in the churches of modern times -- Worship in the churches of the future.
Includes bibliographical references (p. 181-188) and index.
Keywords: Public worship -- History; Liturgics -- History; North America -- Religious life and customs